Management of Pregnant Women with Complaints of Increased Frequency of Urination in Clinics and Maternity Homes: Tatalaksana pada Ibu hamil dengan Keluhan Peningkatan Frekuensi Berkemih di Klinik Dan Rumah Bersalin - Agustina, Yofi Citra; Cholifah, Cholifah; Azizah, Nurul (Universitas Muhammadiyah Sidoarjo, 2020)
Pregnancy is the stage that starts from the products of conception to the birth canal. Normal gestational age is 9 months 7 days or 40 weeks. Pregnant women are obliged to carry out ANC or pregnancy visits to health workers to detect as early as possible if there are abnormalities or complications. This care is carried out at the Afifa Maternity Clinic and Maternity Home, Prambon sub-district, Sidaorjo. Techniques for assessing data by means of patient interviews, physical examinations, analysis, documentation by comparing theories and cases in the field. The results of the report that the author did was to conduct a midwifery assessment of pregnant women with complaints of increased frequency of urination from data processing using SOAP to development. Mother complains of frequent urination in the third trimester is a physiological thing. The care carried out is by explaining the results of the examination, the causes, how to deal with it, the mother's recommendation to rest, reminding the signs of labor, preparation for delivery and pregnancy visits.